A VERSION APPLICATION FOR A CHILD OPPOSITE THE LAW - Azmiati Zuliah; Dian Hardian Silalahi; Adi Putra; Rilawadi Sahputra (Universitas Dharmawangsa Medan, 2022)
AbstractAll children are entitled to live, to grow, to thrive and to be protected from violence and discrimination. In reality, though, the number of children with legal problems increases significantly over the years. The treatment of children in trouble with the law suggests that they are often treated as